Creep Investigations of the Lignostone Under Tension and Torsion - Czech, M. (Engineering Transactions, 1993)
Specimens of the beech-wood lignostone are tested for creep under simple tension along the grains and torsion at room temperature. The creep strains 2Е12(t) generated by pure torsion in the shearing stress range σ12 = (0.4 – 0.6)R12 (where R12 is the shearing strength) are found to be nonlinear. Similarly, the creep strains ε11(t) generated by simple tension in the normal stress range σ11 = (0.2 ∕ 0.35) R11 where R11 is the tensile strength, are also nonlinear. To describe those nonlinear behaviour the nonlinear viscoelasticity theory is employed and the similarity of the creep curves is used. Correct description of the considered phenomena is obtained.